Pengaruh Harga Tiket dan Fasilitas terhadap Loyalitas Wisatawan di Dirja Park Karawang - Dina Herlina; Friska Natalia Purba; Feby Febrianti; Ajat Sudrajat (Jurnal Informatika Ekonomi Bisnis, 2025)
Dirja Park Karawang is a new tourist attraction in Karawang that is starting to grow rapidly. One of the important factors in the development of this tourist spot is how the manager sets ticket prices and provides adequate facilities. Therefore, this research aims to study how ticket prices and facilities affect tourist loyalty partially and simultaneously. This quantitative study involved a survey of 100 respondents who have visited Dirja Park at least twice. The findings of this study indicate that ticket prices and facilities partially and significantly influence tourist loyalty. Data was collected through a closed questionnaire arranged on a Likert scale, then analyzed through multiple linear regression method using SPSS software. Facilities proved to have a more dominant influence than ticket prices in shaping loyalty. The coefficient of determination (R²) value of 0.73 indicates that 73% of the change or variation in tourist loyalty can be explained by the two variables studied. The results show that to increase visitor loyalty, managing quality facilities and the right pricing strategy is very important. It is hoped that this research will help local destination managers improve competitiveness and sustainable tourism experiences.